The functional study of Oryzacystatin-1 protease inhibitor under salinity stress in Malaysian rice cultivar - Mohamad, Nur Haziqah (2015)
Phytocystatin is a protein that encodes cysteine proteinase inhibitor. It is well known for its antipathogenic properties and responsible in plant stress tolerance. Proline is an amino acid that acts as osmoprotectant in plant. Previously, both phytocystatin and proline show response in plant abiotic stresses and have become a potential strategy in combating abiotic stress. In this study, we reported the isolation and characterization of Oryzacystatin-1 (OC-1) gene from Malaysian cultivar of Oryza sativa L., the gene expression profiling by using RT-PCR and the accumulation of proline in stress-induced rice plantlets of MR211, MR220 and MR219. Three Malaysian rice (Oryza sativa L.) cultivars , MR 211, MR 220 and MR 219 were tested in pot culture under different salinity concentration (0, 4, 8, 12 dS m-1) and five different duration of salinity treatment (0, 3, 6, 9, 24 hr) for molecular and biochemical response. All the tests were conducted in randomized complete block design with three replicates in a culture room. The result showed that, the OC-1 gene expression level and proline content were influenced by salinity stress. A cDNA fragment encoding phytocystatin, OC-1 was also isolated. Sequence analysis shows that OC-1 contain all common motifs found in phytocystatin such as a single G residue, QVVAG sequence and PW dipeptide motif. The presence of several cystatin superfamily was proven through Protein BLAST confirming the OC-1 gene isolation earlier. Then, phylogeny studies have shown that the OC-1 gene is closely related to phytocystatin from Zea mays and Coix lacryma-jobi.